ChemInform Abstract: Facile and Eco‐Friendly Synthesis of Chromeno[4, 3‐b]pyrrol‐4(1H)‐one Derivatives Applying Magnetically Recoverable Nano Crystalline CuFe2O4 Involving a Domino Three‐Component Reaction in Aqueous Media. Issue 42 (September 2016) - Saha, Moumita; Pradhan, Koyel; Das, Asish R.
Abstract: The catalyst can be reused for at least six runs without significant loss of activity.